O governo brasileiro e a cooperação Sul-Sul com Moçambique no campo da saúde pública - Lopes, Roberta Nunes (2013)
This dissertation, developed within the Master’s Degree in Administration at the University of Grande Rio (UNIGRANRIO), is based on the literature review of policy transfer, and aims to discuss the process of internationalization of Brazilian public health policies to Mozambique, thus focusing on Brazil's role as a major actor of South-South Cooperation. The dissertation is divided as follows: in Chapter 1, we contextualize the North-South Cooperation, the emergence and evolution of South-South cooperation and how it fits into Brazilian foreign policy agendas. In Chapter 2, we analyze the development of public policies in Brazil after 1988, we debate the theoretical framework of policy transfer and the actual process of transferrings of Brazilian public health policies. In Chapter 3, we present the methodological procedures for the empirical study, showing an overview of the dilemmas of development in Mozambique, we also analyze how the North-South and South-South Cooperation present themselves in Mozambique, emphasizing the Brazilian official development and technical cooperation. Further to this, we analyze the ten public health projects being developed by Brazilian government in Mozambique, one of which gave us scope to engage in a case study on “Sociedade Moçambicana de Medicamentos”. Finally, we conclude that the Brazilian technical cooperation is part and parcel of Brazil’s foreign policy agenda, profiling itself as soft power for the Brazilian international projection. We also found that this Brazilian technical cooperation program is demand-driven and does not impose political conditionalities.